Perspektif Opini Audit : Etika Profesi dan Kompetensi Auditor - Suhayati, Ely; Dita Rizki Rachmawati (Fakultas Ekonomi dan Bisnis Universitas Komputer Indonesia, 2025)
A public accountant must use professional ethics in carrying out his duties and have the competence to be able to provide appropriate audit results for a company's financial statements. The aim of this research is to empirically test the influence of Professional Ethics and Competence on Audit Opinions in Public Accountants who work in Public Accounting Firms in Bandung City. To support this research, the method used is descriptive and verification analysis with a quantitative approach. The population in this study was Public Accountants at Public Accounting Firms in Bandung City which were registered with the OJK. The sample was carried out using non-probability sampling, namely purposive sampling so that the sample was carried out on 30 auditors in 10 Public Accounting Firms in Bandung City using primary data with survey method data collection techniques via questionnaires. The data analysis method used in this research is multiple linear regression analysis using SPSS 20.0 for Windows software. The research results show that Professional Ethics and Competency have a significant effect on Audit Opinion.